Relative abundance of insect visitors on flowers of major subtropical fruits in Himachal Pradesh and their effect on fruit set - Bhatia, Ranjeet; Gupta, Divender; Chandel, J S; Sharma, N K (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1992 und 1993 to study relative abundance of insect visitors on flowers ’ Dashehari’ mango (Magnifera Indica L.), ’Dehradun’ litchi (Litchi chinensis Son.,) and citrus (Citrus spp.), and their effect on fruit set. Out of 34 insect species recorded on the flowers of loose-skinned mandarin or santara (Citrus reticulata Blanco), malta (C. sinensis (L.) Osbeck), kinnow mandarin (C. nobilis lour. x C. deliciosa Tenore), mango and litchi, 15 belonged to Diptera, 13 to Hymenoptera, 4 to Coleoptera and 1 each to Ledipotera and Hemiptera. Of these insect species, italian honeybee (Apis mellifera L.) was the main pollinator in Citrus spp., little-bee (A. florea L.) and hover-fl; (Episyrphus 1betreatus Deg.) on litchi and flies belonging 10 family Calliphoridae (order Diptera) on mango, Mango proved to be highly cross-pollinated crop with maximum increase (infinite) in fruit set (%), followed by malta ( 193.47) and litchi (148.12) with pollinators.